Creating a Financially Healthy Motorcycle Workshop with Structured Accounting - Yenny Wati; Yusrizal Yusrizal; Helly Aroza Siregar; Yusnita Octafilia; Bord Nandre Aprila (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Micro, Small, and Medium Enterprises (MSMEs) that repair motorcycles in Pekanbaru confront financial management issues, particularly in providing accurate and meaningful financial reports. A lack of awareness of basic accounting principles and regular financial recording procedures makes it difficult to measure the financial performance of a business. This community service project seeks to help motorcycle repair MSMEs develop their understanding and skills in creating financial reports in compliance with accounting standards. PKM activities for motorcycle repair shop MSMEs in Pekanbaru, involving the owner or manager and three staff, will occur on-site on Wednesday, March 5, 2025, using lecture, practice, and discussion approaches. Pre- and post-tests are used to examine participants' enhanced understanding, and satisfaction surveys are used to assess activity effectiveness. Following this training session, participants' knowledge of financial report preparation was enhanced by 75%. Participants' skills improve through a learning approach that blends theoretical underpinnings from lectures, practical application of exercises, and collaborative problem-solving through discussion. This PKM activity can help to increase the economic value of motorcycle repair MSMEs by improving financial management and making more informed decisions. This activity also helps to grow and support MSMEs, which are an essential part of the economy. Usaha Mikro, Kecil, dan Menengah (UMKM) bengkel motor di Pekanbaru menghadapi tantangan dalam pengelolaan keuangan, terutama dalam penyusunan laporan keuangan yang akurat dan relevan. Kurangnya pemahaman tentang prinsip-prinsip akuntansi dasar dan metode pencatatan keuangan yang sistematis menyebabkan kesulitan dalam mengukur kinerja keuangan usaha. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan keterampilan UMKM bengkel motor dalam menyusun laporan keuangan yang sesuai dengan standar akuntansi. Kegiatan PKM yang ditujukan untuk UMKM bengkel motor di Pekanbaru, yang melibatkan pemilik atau pengelola dan tiga orang karyawan, akan dilaksanakan secara tatap muka pada Rabu, 5 Maret 2025 dengan metode ceramah, praktik, dan diskusi. Evaluasi dilakukan melalui pre-test dan post-test untuk mengukur peningkatan pemahaman peserta, serta survei kepuasan untuk menilai efektivitas kegiatan. Pemahaman peserta mengenai penyusunan laporan keuangan meningkat sebesar 75% setelah mengikuti kegiatan ini. Keterampilan peserta berkembang melalui pendekatan pembelajaran yang menggabungkan dasar teori dari ceramah, aplikasi praktis dari latihan, dan kolaborasi untuk mengatasi tantangan melalui diskusi. Kegiatan PKM ini dapat berkontribusi pada peningkatan nilai ekonomis UMKM bengkel motor melalui pengelolaan keuangan yang lebih baik dan pengambilan keputusan yang lebih tepat. Kegiatan ini juga berkontribusi pada pertumbuhan dan keberlanjutan UMKM, yang merupakan salah satu pilar penting perekonomian.